A living biobank of matched pairs of patient-derived xenografts and organoids for cancer pharmacology - Xu, Xiaoxi; Kumari, Rajendra; Zhou, Jun; Chen, Jing; Mao, Binchen; Wang, Jingjing; Zheng, Meiling; Tu, Xiaolong; An, Xiaoyu; Chen, Xiaobo; Zhang, Likun; Tian, Xiaoli; et al. (PloS one, 2023)
Patient-derived tumor xenograft (PDX)/organoid (PDO), driven by cancer stem cells (CSC), are considered the most predictive models for translational oncology. Large PDX collections reflective of patient populations have been created and used extensively to test various investigational therapies, including population-trials as surrogate subjects in vivo . PDOs are recognized as in vitro surrogates for patients amenable for high-throughput screening (HTS). We have built a biobank of carcinoma PDX-derived organoids (PDXOs) by converting an existing PDX library and confirmed high degree of similarities between PDXOs and parental PDXs in genomics, histopathology and pharmacology, suggesting “biological equivalence or interchangeability” between the two. Here we demonstrate the applications of PDXO biobank for HTS “matrix” screening for both lead compounds and indications, immune cell co-cultures for immune-therapies and engineering enables in vitro/in vivo imaging. This large biobank of >550 matched pairs of PDXs/PDXOs across different cancers could become powerful tools for the future cancer drug discovery.